2008
DOI: 10.1091/mbc.e08-02-0123
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Remodeling Complexes Interact Dynamically with a Glucocorticoid Receptor–regulated Promoter

Abstract: Brahma (BRM) and Brahma-related gene 1 (BRG1) are the ATP-dependent catalytic subunits of the SWI/SNF family of chromatin-remodeling complexes. These complexes are involved in essential processes such as cell cycle, growth, differentiation, and cancer. Using imaging approaches in a cell line that harbors tandem repeats of stably integrated copies of the steroid responsive MMTV-LTR (mouse mammary tumor virus-long terminal repeat), we show that BRG1 and BRM are recruited to the MMTV promoter in a hormone-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 88 publications
2
78
0
Order By: Relevance
“…Components of the SWI/SNF complex bind to various nuclear receptors, such as those of estrogen, progesterone, androgen, glucocorticoids (GCs) and retinoic acid (RA), thereby adapting the gene expression programs to the demands of the cell environmental requirements. [14][15][16][17][18] RA and GC are well-known modulators of cell differentiation, embryonic development and morphogenesis 19 and are used therapeutically to treat some types of cancers. GC are part of the curative treatment of acute lymphoblastic leukemia while RA is the therapeutic agent for some neuroblastomas and acute promyelocytic leukemia, which both carry the promyelocytic leukemia-RA receptor alpha gene fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Components of the SWI/SNF complex bind to various nuclear receptors, such as those of estrogen, progesterone, androgen, glucocorticoids (GCs) and retinoic acid (RA), thereby adapting the gene expression programs to the demands of the cell environmental requirements. [14][15][16][17][18] RA and GC are well-known modulators of cell differentiation, embryonic development and morphogenesis 19 and are used therapeutically to treat some types of cancers. GC are part of the curative treatment of acute lymphoblastic leukemia while RA is the therapeutic agent for some neuroblastomas and acute promyelocytic leukemia, which both carry the promyelocytic leukemia-RA receptor alpha gene fusion.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SWI/SNF complexes in nuclear receptor (NR)-mediated transcriptional activation was first studied for the glucocorticoid receptor in a heterologous yeast model system and later in mammalian cells (3,6,7). SWI/SNF complexes play critical roles in establishing hypersensitive chromatin architecture associated with steroid hormone receptor binding sites on DNA and are recruited to these sites in a hormone-dependent manner (4,8,9).…”
mentioning
confidence: 99%
“…It has been suggested that estrogen receptor ␣ recruits the BRG1 complex through the BRG1 complex subunit BAF57 (36). Transcriptional dependence for BRG1 activity has also been observed for GR-responsive promoters including mouse mammary tumor virus, p21, and 11␤-hydroxysteroid dehydrogenase type 2 (11,37). Studies examining hormone-mediated transcriptional activation of mouse mammary tumor virus have shown that the progesterone receptor can compete with GR for available BRG1, resulting in inhibition of GR-mediated transactivation (38).…”
Section: Discussionmentioning
confidence: 99%